2016
DOI: 10.1111/imb.12272
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of the distinct expression profiles of candidate chemosensory membrane proteins in the antennal transcriptome of Adelphocoris lineolatus (Goeze)

Abstract: Chemosensory membrane proteins, including odorant receptors (ORs), ionotropic receptors (IRs), gustatory receptors (GRs) and sensory neurone membrane proteins (SNMPs), are supposed to be crucial macromolecules in the insect olfactory signal transduction pathway. The alfalfa plant bug Adelphocoris lineolatus (Goeze) (Hemiptera: Miridae) is highly attracted to high-nitrogen or flowering plants and destroys many important agricultural crops. We assembled the antennal transcriptome of A. lineolatus using Illumina … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 63 publications
(84 reference statements)
1
19
0
Order By: Relevance
“…It is similar to the case of Triatoma brasiliensis , which has three contigs that encode ORs in the reference transcriptome of female and male. The number of ORs in P. solenopsis is smaller than that in other hemiptera insects, such as Adelphocoris linoleates (88 ORs in the antennae) (Xiao et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…It is similar to the case of Triatoma brasiliensis , which has three contigs that encode ORs in the reference transcriptome of female and male. The number of ORs in P. solenopsis is smaller than that in other hemiptera insects, such as Adelphocoris linoleates (88 ORs in the antennae) (Xiao et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The plant mirid species of Lygus spp., Adelphocoris spp., and other species strongly rely on olfactory cues to regulate their chemical perception behaviors. Series of studies on chemoreception of plant mirids were reported such as antennal morphological and electrophysiological characteristic (Chinta et al, 1997 ; Sun et al, 2014a ), putative odorants (Koczor et al, 2012 ; Sun et al, 2013 ), physiological functions of OBPs (Gu et al, 2011 ; Hull et al, 2014 ; Sun et al, 2014b ) and conventional ORs (Yan et al, 2015 ; An et al, 2016 ; Xiao et al, 2016 ; Zhang et al, 2016 ). In the current study, we focused on the evolutionary divergence of Orco orthologs among plant bug species from distinct geographic regions of China.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, 66 ORs were identified in the antennae of Y. signatus. This number is much lower than that for other Hemipteran insects, such as 83 ORs in Nysius ericae (Zhang et al, 2016), 110 ORs in A. lucorum (An et al, 2016), and 88 ORs in Adelphocoris lineolatus (Xiao et al, 2017); however, it is higher than 63 ORs in Sogatella furcifera (He et al, 2015) and 45 ORs in Aphis gossypii (Cao et al, 2014). This may be caused by the adaptation of distinct species to their hosts during evolution.…”
Section: Discussionmentioning
confidence: 77%